Do the citizens of Europe trust their police?. Issue 1 (13th July 2015) - Shankar Sankaran, Professor; Barton, Harry; Beynon, Malcolm J
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The maintenance of public order and the control of crime are clearly amongst the primary objectives of global law enforcement agencies. An important antecedent to this is the consideration of public trust in their police force. The purpose of this paper is to utilise data from the fifth round European Social Survey (ESS), to investigate how public social indicators may be highlight the level of trust in a country's police force. Design/methodology/approach – The results from the ESS are analysed using fuzzy-set Qualitative Comparative Analysis (fsQCA), multiply conjunctional causal configurations of the considered social indicators are then established and analysed. Findings – A consequence of using fsQCA, asymmetric causal configurations are identified for the relative high and low limiting levels of trust towards the police in the considered countries. The results offer novel insights into the relationship between social indicators and police trust, as well as expositing a nascent technique (fsQCA) that may offer future potential in this area. Originality/value – This paper introduces a nascent technique (fsQCA) to analyse a major European data set relating to citizens perceptions of the police. The findings might prove useful for policing organisations as they develop strategies to maintain/improve the level of trust and confidence of citizens in the policing services they provide.